H.B. Jassin : harga diri sastra Indonesia - Sofyan, Oyon. (Magelang : IndonesiaTera bekerjasama sama dengan Lingkar Mitra Yayasan Dokumentasi Sastra H.B. Jassin, 2001)
Festschrift in honor of Hans Bague Jassin, 1917-2000, an Indonesian writer.
Includes bibliographical references and index.
Keywords: Jassin, H. B., -- 1917-2000.; Authors, Indonesian -- Biography; Critics -- Indonesia -- Biography